The Role Of Social Services In Managing Households and Beggers in Tanjungpinang City - Selvia Evayanti Saragih; Qorina Salsabila; Gabriela Purba (PT. Publikasiku Academic Solution, 2022)
Background: Beggars are one of them, and is one of the negative impacts of development, especially urban development. Begging in cities like Tanjung Pinang is a phenomenon that is recognized as a serious problem, especially considering the population. Aim: The Tanjungpinang City Social Service aims to deal with beggars with regulations, provide shelter, and educate the public about the prohibition of distributing cash to beggars. The Tanjungpinang City Social Service is not yet fully ready to handle beggars. Method: Using qualitative research is based on natural conditions in the field and does not involve extensive data manipulation, so as to produce data with true meaning. Types of Research Descriptive research usually uses analysis. Findings: The result of this research is that the problem of beggars is a serious concern of the government, and various efforts have been made to overcome it.